2020
DOI: 10.11591/ijeecs.v17.i1.pp36-46
|View full text |Cite
|
Sign up to set email alerts
|

Solar powered peltier cooling storage for vaccines in rural areas

Abstract: The research presented in this paper proposes a new design of a vaccine cooling and storage unit that can keep vaccines in the cold chain (2°C to 8°C). This design was done to facilitate effective completion of the African vaccination week. The cooling and storage unit was designed to be compact, portable, well isolated and to make use of a PV solar energy system as a source of electricity. The cooling unit makes use of a Liquid to Air thermoelectric cooling module connected to some tubing and a liquid pump to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…This technology generally integrates solar energy power generation systems ( Alfariani and Pratama, 2018 ). With this concept, Buitendach, Jiya, and Gouws succeeded in creating a portable storage unit that tends to last up to 72 h (3 days) with a temperature control accuracy of 1 °C and a capacity of up to 250 vials ( Buitendach et al, 2019 ). Al-Madhhachi and Al-Najideen (2020), with COMSOL Multiphysics technology, also succeeded in developing a storage unit by utilizing a lower solar panel power of 70 watts ( Al-Madhhachi and Al-Najideen, 2021 ).…”
Section: Latest Inventions and Innovationsmentioning
confidence: 99%
“…This technology generally integrates solar energy power generation systems ( Alfariani and Pratama, 2018 ). With this concept, Buitendach, Jiya, and Gouws succeeded in creating a portable storage unit that tends to last up to 72 h (3 days) with a temperature control accuracy of 1 °C and a capacity of up to 250 vials ( Buitendach et al, 2019 ). Al-Madhhachi and Al-Najideen (2020), with COMSOL Multiphysics technology, also succeeded in developing a storage unit by utilizing a lower solar panel power of 70 watts ( Al-Madhhachi and Al-Najideen, 2021 ).…”
Section: Latest Inventions and Innovationsmentioning
confidence: 99%
“…In this research, fuzzy logic control was used in a specific prototype project to obtain specific results. Vaccine storage in rural areas with Peltier cooling powered by solar that can keep vaccines cold chain (2 °C to 8 °C) [19]. But this research updated it from 2°C to 16°C so that it becomes useful for insulin too [20].…”
Section: Introductionmentioning
confidence: 99%
“…Hot temperatures in a space must be removed to achieve a thermal comfort zone [6]- [9]. The previous researcher found that the Peltier module can cool down temperature and develop it as a portable air conditioner [10]- [13]. It is proven to overcome waste energy consumption in portable air conditioning, Peltier module was used.…”
Section: Introductionmentioning
confidence: 99%